SISTEM MONITORING TINGKAT KEKERUHAN AIR PADA FILTER DAN LAJU AIR POMPA MENGGUNAKAN APLIKASI BLYNK DI PROKLAMATOR KOI BLITAR, JAWA TIMUR - Dio Tri Pamungkas; Hadi Suyono; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
Water quality is important for koi fish health and is affected by the condition of the filter pond. The filter pond filters dirty water and delivers clean water to the pond so the cleanliness of the filter pond can be seen from the turbidity level of the water. The water pump is used to circulate water and it is important to perform maintenance on the water pump so that there is no decrease in performance. A monitoring system is needed using turbidity sensors and water flow sensors, and can be accessed via Android smartphones using Blynk. Each sensor is tested to test the difference value with the measuring instrument on each sensor. The turbidity sensor gets an average difference value of 2.31% and the water flow sensor gets an average difference value of 0.61%. This means that the sensor can read each parameter well. In addition, testing for the difference value of data transmission and notification on LCD and Blynk. Data transmission gets a difference value of 0% which means that the data sent by ESP32 can be displayed on LCD and Blynk and has no delay. Keywords: Water Quality, Water Turbidity Level, Water Flow, ESP32, Blynk Daftar Pustaka[1] Almumtazah, N., Azizah, N., Putri, Y. L., & Novitasari, D. C. R. (2021). Prediksi Jumlah Mahasiswa Baru Menggunakan Metode Regresi Linier Sederhana. Jurnal Ilmiah Matematika Dan Terapan, 18(1), 31–40. https://doi.org/10.22487/2540766x.2021.v18.i1.15465[2] Babiuch, M., Foltynek, P., & Smutny, P. (2019, May 1). Using the ESP32 Microcontroller for Data Processing. Proceedings of the 2019 20th International Carpathian Control Conference, ICCC 2019. https://doi.org/10.1109/CarpathianCC.2019.8765944[3] Berlianti, R., & Fibriyanti. (2020). Perancangan Alat Pengontrolan Beban Listrik Satu Phasa Jarak Jauh Menggunakan Aplikasi Blynk Berbasis Arduino Mega. Sain, Energi Teknologi & Industri, 5, 17–26.[4] Febbiyana, W., Kurniawan, S., Isnen, M., & Anugrah, S. (2019). Pembuatan Alat Test dan Kalibrasi Flowmeter Solar pada Pabrik Pemanggangan Anoda PT INALUM. Jurnal Elektronika, Listrik Dan Teknologi Informasi Terapan, 2(1), 43–49. https://ojs.politeknikjambi.ac.id/elti[5] Trianggana, D. A. (2020). Peramalan Jumlah Siswa- Siswi Melalui Pendekatan Metode Regresi Linear. Jurnal Media Infotama, 16(2).[6] Yuliara, I. M. (2016). Regresi Linier Sederhana.[7] WANTIMPRES. (2017, April 27). Dewan Pertimbangan Presiden. Dipetik Mei 29, 2022, dari Potensi Perikanan Indonesia:https://wantimpres.go.id/id/potensiperikanan-indonesia/[8] Farm, A. K. (2019, Agustus 28). Perawatan Filter Kolam. DIpetik Agustus 4, 2022, dari Agro Koi Farm: https://www.agrokoifarm.com/perawatan-filter-kolam/[9] Putrawan, I. G. H., Rahardjo, P., & Agung, I. G. A. P. R. (2019). Sistem Monitoring Tingkat Kekeruhan Air dan Pemberi Pakan Otomatis pada Kolam Budidaya Ikan Koi Berbasis NodeMCU. Majalah Ilmiah Teknologi Elektro, 19(1), 1. https://doi.org/10.24843/mite.2020.v19i01.p01[10] Maharani, S. H., & Kholis, N. (2020). Studi Literatur: Pengaruh Pengunaan Sensor Gas Terhadap Presentase Nilai ErrorKarbonmonoksida (CO) dan Hidrokarbon (HC) Pada Prototipe Vehicle Gas Detector (VGD). Jurnal Teknik Elektro, 09, 569–578.